Empowering Women in Entrepreneurship: A Global Perspective on Socio-Economic Factors and Policy Interventions - Astrid Laksmita Djati; Meylisa Eka Putri; Andriyani; Intan Ratnawati (Arthatama: Journal of Business Management and Accounting, 2023)
This study explores the role of women’s empowerment in promoting entrepreneurship, with a focus on how various socio-economic factors influence female entrepreneurship globally. Women’s economic and social empowerment has become an essential component of sustainable development, contributing significantly to reducing poverty and fostering community development. The research highlights key factors that enable women to engage in entrepreneurial activities, such as access to financial resources, education, mentorship, and the dismantling of socio-cultural barriers. The method used in this research includes a qualitative literature review and data analysis through a descriptive approach. By examining previous studies from different countries, including Indonesia, India, and South Africa, the study provides valuable insights into the impact of financial inclusion, government interventions, and self-help groups on women’s entrepreneurial success. Additionally, it emphasizes the importance of empowering women through educational programs and institutional support to foster greater participation in the economy. The findings suggest that women’s empowerment is not only critical for personal and household economic growth but also for enhancing broader social and economic development. The study also identifies the challenges faced by women entrepreneurs and offers recommendations to address these obstacles for more effective empowerment policies.